2010
DOI: 10.1055/s-0030-1255118
|View full text |Cite
|
Sign up to set email alerts
|

Social Functioning and Self-Esteem in Young People with Disabilities Participating in Adapted Competitive Sport

Abstract: Social functioning scores were significantly higher in this population than in the samples of young people with disabilities available in the literature. Interactions between self-concept, social functioning quality of life and participation in adapted sport activities require further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
2
8
0
2
Order By: Relevance
“…Dinomais et al investigated social functioning, quality of life and self-esteem in 496 young athletes with disabilities taking part in adapted competitive sports. The researchers noticed significantly higher social functioning scores in this population, which confirms the positive effect of sport on the general well-being of physically people with disabilities [ 32 ].…”
Section: Discussionsupporting
confidence: 62%
“…Dinomais et al investigated social functioning, quality of life and self-esteem in 496 young athletes with disabilities taking part in adapted competitive sports. The researchers noticed significantly higher social functioning scores in this population, which confirms the positive effect of sport on the general well-being of physically people with disabilities [ 32 ].…”
Section: Discussionsupporting
confidence: 62%
“…A study of 131 mobility impaired athletes who played either wheelchair rugby or wheelchair basketball found that playing an additional year of adaptive sport was associated with an approximately 4% increase in the likelihood of employment and concluded that a substantial economic benefit would result from increased participation in adaptive sport by people with mobility impairments (Lastuka & Cottingham, 2015). Other key psychosocial benefits of sports participation include: higher satisfaction with life scores in people with spinal cord injury and other physical disabilities (Tasiemski, Kennedy, Gardner, & Taylor, 2005; Yazicioglu, Yavuz, Goktepe, & Tan, 2012); enhanced quality of life in war veterans with disabilities and community-dwelling people with physical disabilities(Laferrier, Teodorski, & Cooper, 2015; Yazicioglu et al, 2012); higher self-esteem (Laferrier et al, 2015); improved social functioning in people with disabilities (Dinomais et al, 2010); and improved social integration in people with spinal cord injury (Hanson, Nabavi, & Yuen, 2001; McVeigh, Hitzig, & Craven, 2009).…”
Section: Performance-focussed Sports Trainingmentioning
confidence: 99%
“…6 Indirect improvement in life satisfaction might be due to improved exercise capacity, which seems to be positively correlated with improved functional independence, lower levels of depression, higher social status, and improved self-esteem in persons with SCI. 38,42 Moreover, genetics could influence both life satisfaction and exercise capacity in the general population. 41 Altogether, the findings in the literature support our findings of a positive relationship between wheelchair exercise capacity and life satisfaction.…”
Section: Exercise Capacity and Quality Of Life In Sci Patientsmentioning
confidence: 99%